The Comparison of the Criminal Code and Draft Criminal Code Formulations of Crimes against Religion and Religious Life - Candra, Septa; Huda, Chairul (Jurnal Cita Hukum, 2022)
The formulation of criminal acts against religion and religious life in Indonesian laws and regulations still leaves various problems. This article discusses the form of formulation of criminal offenses against religion and religious life in the upcoming Criminal Code and RKUHP. The form of this research is normative juridical with legal, conceptual and case approaches. The results of this study indicate that the RKUHP has made changes that lead to "concretization" and "objectification" of crimes against religion and religious life, so that the principles of lex certa and lex stricta are truly considered. The RKUHP has also been more advanced in formulating crimes against religion and religious life based on the notion of respect for the right to religion as a human right protected by the Constitution. Hopefully the enactment of the RKUHP can be a solution in law enforcement against various crimes against religion and religious life in Indonesia in the future.